Welcome notes Head of Centre of Studies / Johanudin Lahap @ Wahab - Lahap @ Wahab, Johanudin (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2019)
I would like to take this opportunity to thank all staff members for their hard work, determination and painstaking towards the achievement throughout the year of 2018. The year of 2018 is the year of glory where the Faculty of Hotel & Tourism Management UiTM Penang Branch had clinched several prestigious awards and they are, The Pearl Award (The Best Faculty 2017), Golden International Award, Golden Talent Award and Golden Research and Publication Award. The faculty member also won several awards from multiple International Exhibitions and Innovation around the country. These awards are a manifestation of achievement and hard work from everyone. It accordingly imperative to recognize staff achievement and they certainly make the faculty proud. Several initiatives were executed to achieve success such a frequent workshop for staff on publications, journals, proceedings, books and consultations. The faculty also involved with many community services, charities and corporate service responsibility locally and internationally. Several faculty's members were also appointed by local and international bodies and universities to be international editorial board, examiner, consultant and leading experts etc.